1158. Needlestick Injuries and Other Potential Exposures to Bloodborne Pathogens Among Police Officers in a City Police Department, 2011–2016. (26th November 2018) - De Perio, Marie; Victory, Kerton; Groenewold, Matthew
Abstract: Background: The approximately 850, 000 police officers nationwide are at risk of bloodborne diseases through needlestick injuries and other exposure incidents because of the nature of their work. In response to a request for a health hazard evaluation, we determined the incidence and circumstances of needlestick injuries and other potential exposures to bloodborne pathogens among police officers at a city department from 2011 to 2016. Methods: We analyzed data extracted from the city's centralized human resource database on all needlestick injuries and other potential exposure incidents from January 1, 2011 to December 31, 2016 and characterized their circumstances. We calculated the annual incidence of needlestick injuries using two methods. We ran a Poisson regression model to determine the trend in the annual incidence over time using SAS 9.4. Results: We identified 13 needlestick injuries and 37 additional potential exposure incidents. Needlestick injuries most commonly occurred during pat-down searches of a suspect and during search of a suspect's property or vehicle. Nine of 11 source persons with documented test results after a needlestick injury were found to have hepatitis C infection. The annual incidence of needlestick injuries ranged from 0 to 5.07 per 1, 000 police officers and from 0 to 2.45 per 10, 000 reactive calls for service and did not appear to have a significant trend. Most exposure incidents consisted of spitting incidents, human bites, and other contact with blood. Of 22 source persons with blood drawn, four had hepatitis C infection, two have HIV infection, and one had both. None of the incidents reportedly led to transmission of hepatitis B, hepatitis C, or HIV. Conclusion: Police officers in this department are at risk for needlestick injuries and other exposures to bloodborne pathogens. We recommended improvements to engineering, administrative, and personal protective equipment controls, including training on safe searching techniques and sharps evidence collection and provision of nitrile gloves. Disclosures: All authors: No reported disclosures.